Delayed cerebral ischemia and spreading depolarization in absence of angiographic vasospasm after subarachnoid hemorrhage - Woitzik, Johannes; Münch, Elke; Schmiedek, Peter (Journal of cerebral blood flow & metabolism, 2012)
It has been hypothesized that vasospasm is the prime mechanism of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH). Recently, it was found that clusters of spreading depolarizations (SDs) are associated with DCI. Surgical placement of nicardipine prolonged-release implants (NPRIs) was shown to strongly attenuate vasospasm. In the present study, we tested whether SDs and DCI are abolished when vasospasm is reduced or abolished by NPRIs. After aneurysm clipping, 10 NPRIs were placed next to the proximal intracranial vessels. The SDs were recorded using a subdural electrode strip. Proximal vasospasm was assessed by digital subtraction angiography (DSA). 534 SDs were recorded in 10 of 13 patients (77%). Digital subtraction angiography revealed no vasospasm in 8 of 13 patients (62%) and only mild or moderate vasospasm in the remaining. Five patients developed DCI associated with clusters of SD despite the absence of angiographic vasospasm in three of those patients. The number of SDs correlated significantly with the development of DCI. This may explain why reduction of angiographic vasospasm alone has not been sufficient to improve outcome in some clinical studies.